2020
DOI: 10.3389/fped.2020.00433
|View full text |Cite
|
Sign up to set email alerts
|

When the Cough Does Not Improve: A Review on Protracted Bacterial Bronchitis in Children

Abstract: Chronic cough is defined as a daily cough that persists longer than 4 weeks. Protracted bacterial bronchitis (PBB) is a common cause of chronic wet cough in preschool children with no symptoms or signs of other specific causes, and resolution usually follows a 2-week course of an appropriate oral antibiotic. The diagnosis is mainly clinical; generally, no instrumental examinations are necessary. The most common bacteria found in the bronchoalveolar lavage (BAL) of subjects with PBB include Haemophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
2
18
0
6
Order By: Relevance
“…Similar to other studies, the clinical symptoms in most of the children were significantly ameliorated after BAL. 37 Our study also showed that children with patchy opacities observed via CT had good absorption of inflammatory lesions after elective follow-up BAL.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to other studies, the clinical symptoms in most of the children were significantly ameliorated after BAL. 37 Our study also showed that children with patchy opacities observed via CT had good absorption of inflammatory lesions after elective follow-up BAL.…”
Section: Discussionsupporting
confidence: 66%
“…A failure to improve a wet cough after a 4-weeks antibiotic therapy requires more investigations (such as CT scan, bronchoscopy, immunity tests) to rule out the presence of another underlying disease [ 23 ]. In our case, the early diagnosis of NCFB allowed a mild and well-controlled course of the disease since the bronchiectasis detected by HRCT were at a very early radiological stage.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly higher microbial load (figure 1) observed in all of the throat swabs from PID-0001 compared to all other participants corroborates this probable diagnosis (Sibila et al, 2019). In addition, all samples from PID-0001 show the presence of Haemophilus influenzae , whose presence is associated with persistent bacterial bronchitis (Gallucci et al, 2020). These results indicate that the participant may be suffering from bronchiectasis characterized by a general overgrowth of microorganisms in the throat leading to airway and epithelial damage which is the root cause of their cough, as opposed to being caused by a transient pathogenic infection (Martin and Harrison, 2015).…”
Section: Resultsmentioning
confidence: 99%